Company Value Disclosure Based on Fundamental Analysis of Energy Companies in Indonesia - Novitasari, Anggi; Yulizar, Yulizar (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Firm value is needed for companies going public as an effort to obtain investment/funding in business development. The good value of the company indicates a strong market perception, not only among investors, but also the public. Thus, from a business perspective, good corporate value describes two business dimensions, namely good investment funding and profitable business. This study aims to see the role of the company's fundamental financial factors on business quality, so that it has implications for increasing company value. To answer these objectives, a quantitative approach is used based on financial report data. In the test used the method of statistical analysis of linear regression. The object of this research is energy companies in Indonesia which are registered as go public companies. Sources of research data are financial reports taken by purposive sampling technique. A total of 19 companies were used as research samples and more than 75 financial statements were used as research data. The results show that there is a significant difference in the two tests, where in the simultaneous model all financial fundamental factors have a large contribution to firm value. Meanwhile, the partial model test shows smaller/less linear results. In simultaneous testing, one conclusion was found, that the company's value will strengthen if all the main financial instruments in the company are fulfilled. In other words, the company's business must show good sales and profit growth, so that this has an impact on improving the quality of other business instruments, which in turn has implications for market assessment/public perception.